2002
DOI: 10.1055/s-2002-26739
|View full text |Cite
|
Sign up to set email alerts
|

Production of Paclitaxel and Baccatin III in a 20-L Airlift Bioreactor by a Cell Suspension of Taxus wallichiana

Abstract: A cell suspension culture of Taxus wallichiana (Himalayan Yew) was grown in shake flasks and a 20-L airlift bioreactor running for 28 days in a batch mode, and its capacity to accumulate paclitaxel and baccatin III was measured. When both culture types were in the highest productive state (from day 24 to day 28), there was a greater accumulation of paclitaxel and baccatin III in the bioreactor culture than in the shake flask culture (factor of 2.0 and 1.2, respectively). These increases in paclitaxel and bacca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…During culturing, the excretion of both taxanes in cells grown in flasks and in the bioreactor exceeded on average 72% of the total compound content which is consistent with results obtained by Navia-Osorio et al (2002) and Pestchanker et al (1996) although Wickremesinhe & Arteca (1994) reported only a 10% release of paclitaxel in suspension culture of Taxus · media. It was earlier demonstrated that at low inoculum sizes of 1.5 and 2.0 g dry wt l )1 the extracellular paclitaxel concentration was relatively higher (Wang et al 1997) which is in accordance with our results.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…During culturing, the excretion of both taxanes in cells grown in flasks and in the bioreactor exceeded on average 72% of the total compound content which is consistent with results obtained by Navia-Osorio et al (2002) and Pestchanker et al (1996) although Wickremesinhe & Arteca (1994) reported only a 10% release of paclitaxel in suspension culture of Taxus · media. It was earlier demonstrated that at low inoculum sizes of 1.5 and 2.0 g dry wt l )1 the extracellular paclitaxel concentration was relatively higher (Wang et al 1997) which is in accordance with our results.…”
Section: Resultssupporting
confidence: 86%
“…On the other hand, the consumption of sucrose in flasks corresponded well to the cell growth profile, and was 90% exhausted by day 14 --at the onset of stationary growth phase. Navia-Osorio et al (2002) also reported the lack of the lag phase after inoculation in experiments conducted in 20-l bioreactor. Data recorded during cultivating cells in bioreactor might be contributed to higher cell damage by sharing as the medium stirring was set at 400 rpm.…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, tissue culture offers a practical alternative to Taxol production. Being capable of performing a precise control of the production conditions, applying production stimuli such as elicitors and the ease of extraction in short time, are the main advantages of this system [6][7]. The use of elicitors of plant defense mechanisms has been one of the most effective strategies for improving the productivity of Taxol and many other useful secondary metabolites in plant cell cultures [8].…”
Section: Introductionmentioning
confidence: 99%
“…In The Netherlands, van Rozendaal et al, (2000) reported the production of taxol and related taxanes in Taxus species, which include T. globosa as a species with highest content, not only of taxol, but also its precursors, which easily can be chemically bioconverted into cultures of T. baccata L. (Bentebibel et al, 2005), Taxus canadensis (Nikolakakis et al, 2000), in the hybrid Taxus media (Taxus baccata x Taxus cuspidata) (Bonfill et al, 2003) and Taxus wallichiana Zucc., (Navia-Osorio et al, 2002;van Rozendaal et al, 2000).…”
Section: Introductionmentioning
confidence: 99%